2007
DOI: 10.1002/ana.21076
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells effectively modulate pathogenic immune response in experimental autoimmune encephalomyelitis

Abstract: Overall, these findings suggest that the beneficial effect of MSCs in experimental autoimmune encephalomyelitis is mainly the result of an interference with the pathogenic autoimmune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
401
6
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(431 citation statements)
references
References 20 publications
16
401
6
8
Order By: Relevance
“…Here, stem cells extensively interact with the host immune system to inhibit the activation and proliferation of T cells (Gerdoni et al, 2007), the maturation of DCs (Pluchino et al, 2009b), or the emigration of spleen neutrophils toward the damaged brain (Lee et al, 2008). Overall, these pioneering studies demonstrated the therapeutic efficacy of MSCs and NPCs in animal models of inflammatory damage, but left (partly) open the question of whether or not stem cell integration in the nervous system is indispensable for the therapeutic outcomes observed.…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…Here, stem cells extensively interact with the host immune system to inhibit the activation and proliferation of T cells (Gerdoni et al, 2007), the maturation of DCs (Pluchino et al, 2009b), or the emigration of spleen neutrophils toward the damaged brain (Lee et al, 2008). Overall, these pioneering studies demonstrated the therapeutic efficacy of MSCs and NPCs in animal models of inflammatory damage, but left (partly) open the question of whether or not stem cell integration in the nervous system is indispensable for the therapeutic outcomes observed.…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…In EAE model, disease commences by auto-reactive T cells that when are peripherally activated, translocate into CNS, where they are re-activated by local antigen-presenting cells, and recruit additional peripheral pathogenic immune cells to contribute to the demolition of myelin and eventual neurodegeneration (Goverman 2009). Many studies showed that transplantation of BM-MSCs modulates CD4 + T-cell-mediated myelin oligodendroglial glycoprotein peptide ) EAE, and blocks the autoimmune attack against myelin antigens (Zappia et al 2005;Gerdoni et al 2007;Gordon et al 2010;Uccelli and Prockop 2010). These effects were also correlated with reduction of demyelination as well as T-cell infiltration and induction of T-cell anergy and nervous tissue repair by integration into the CNS (Zappia et al 2005;Rafei et al 2009;Gordon et al 2010).…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%
“…Moreover, Gerdoni et al (2007) using the PLP-induced EAE model demonstrated that the intravenous administration of allogenic murine BM-MSCs (2.5 × 10 6 ) reduced inflammatory infiltrates by decreasing production of IFN-γ and tumor necrosis factor (TNF)-α, as well as demyelination and axonal loss. BM-MSCs treatment inhibited also encephalitogenic potential of myelin-reactive T cells by reducing the production of PLP-specific antibodies.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%
See 2 more Smart Citations